Implementation and Evaluation of Algorithms with ALGator - Dobravec, Tomaž (Informatica, 2019)
In this paper we present an automatic algorithm evaluation system called ALGator, which was developed to facilitate the algorithm design and evaluation process. The system enables unbiased tests of the correctness of the algorithm's results on given test cases and comparisons of the quality of implemented algorithms for solving various kinds of problems (e.g. sorting data, matrix multiplication, traveler salesman problem, shortest path problem, and the like). Within the ALGator one can define a problem by specifying the problem descriptors, test sets with corresponding test cases, input parameters and output indicators, algorithm specifications and criteria for measuring the quality of algorithms. When a user of the system submits an algorithm for solving a given problem, ALGator automatically executes this algorithm on predefined tests, measures the quality indicators and prepares the results to be compared with the results of other algorithms in the system. The ALGator is meant to be used by algorithm developers to perform independent quality tests for their solutions.